Genetic transmission networks reveal the transmission patterns of HIV-1 CRF01_AE in China. (7th August 2017) - Li, Xiaoshan; Gao, Rong; Zhu, Kexin; Wei, Feiran; Fang, Kun; Li, Wei; Song, Yue; Ge, You; Ji, Yu; Zhong, Ping; Wei, Pingmin
Abstract : Objectives: The epidemic of HIV-1 CRF01_AE has become a major public health issue in China. This study aimed to characterise the transmission patterns of genetic networks for CRF01_AE nationwide and elucidate possible opportunities for prevention. Methods: We isolated and conducted genetic transmission network analysis of all available CRF01_AE pol sequences (n=4704) from China in the Los Alamos HIV sequence database. Results: A total of 1391 (29.6%) sequences were identified as belonging to 400 separate networks. Of men who have sex with men (MSM) in the networks, 93.8% were linked to other MSM and only 2.4% were linked to heterosexual women. However, 11.8% heterosexual women in the networks were linked to MSM. Lineages composed mainly of MSM had higher transmission than those that were mostly heterosexuals. Of the 1391 individuals in networks, 513 (36.9%) were linked to cases diagnosed in different provinces. The proportion of individuals involved in inter-province links was interrelated with the number of migrant people (Spearman's r =0.738, p =0.001). Conclusions: The outcome of this study could help improve our ability to understand HIV transmission among various regions and risk groups in China, and highlighted the importance of targeting MSM and migrants by prevention and intervention efforts.